2017
DOI: 10.1145/3134689
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Temporal Representations of Alcohol and Tobacco Behaviors from Social Media Data

Abstract: Understanding tobacco- and alcohol-related behavioral patterns is critical for uncovering risk factors and potentially designing targeted social computing intervention systems. Given that we make choices multiple times per day, hourly and daily patterns are critical for better understanding behaviors. Here, we combine natural language processing, machine learning and time series analyses to assess Twitter activity specifically related to alcohol and tobacco consumption and their sub-daily, daily and weekly cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Based on surveillance-like data from Twitter, strategies may be implemented encouraging awareness of the negative consequences of hazardous drinking, delivering a preventive message about BD. Likelihood of targeted behaviour patterns and the identification of target groups or places at high risk for unhealthy behaviours may represent key, high-resolution information to inform relevant stakeholders responsible for preventive policies [63]. Specifically, detecting real users reporting BD and alcohol-related risky behaviours on social media appears as a complex but promising approach deserving a deeper investigation in future studies.…”
Section: Preventive Implications and Conclusionmentioning
confidence: 99%
“…Based on surveillance-like data from Twitter, strategies may be implemented encouraging awareness of the negative consequences of hazardous drinking, delivering a preventive message about BD. Likelihood of targeted behaviour patterns and the identification of target groups or places at high risk for unhealthy behaviours may represent key, high-resolution information to inform relevant stakeholders responsible for preventive policies [63]. Specifically, detecting real users reporting BD and alcohol-related risky behaviours on social media appears as a complex but promising approach deserving a deeper investigation in future studies.…”
Section: Preventive Implications and Conclusionmentioning
confidence: 99%
“…Of the twenty-two papers discussed in this section, three are focussed on opioid abuse [35,41,42], eight on tobacco and marijuana use [6,12,13,40,43,45,46,49], one on alcohol abuse [36], and one on the street drug, mephedrone [44]. Twitter is the most popular source of data (18 papers) [6,11,12,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], with Reddit [11][12][13], and online health communities [12,13], both represented. Supervised machine learning (8 papers -all utilising Twitter data) and unsupervised machine learning (11 papers) were both evident in the reviewed papers, with classical machine learning approaches more common than modern neural-network-based approaches (17 and 2 papers, respectively).…”
Section: Substance Abusementioning
confidence: 99%
“…In addition to these shifts in tobacco use, there have also been substantial changes in the regulation of marijuana products, particularly in the US context, and these changes have led -it has been suggested 6 https://www.cdc.gov/drugoverdose/data/ statedeaths.html [89] -to an increase in marijuana use [90]. Given these public health concerns, using NLP to investigate tobacco, e-cigarette, and marijuana use, has become an active research area, especially to classify discussions [6,12,43,45,46] or to determine whether a particular user is above or below 21 years of age [40]. Reported findings included evidence that Twitter users frequently discussed ways in which e-cigarettes can be used in the workplace in a bid to circumvent smoking bans [43], and evidence that hookah was discussed more frequently at the weekend, indicating its use is associated with leisure activities, while reported tobacco use tends to be more consistent across the week [40].…”
Section: Tobacco E-cigarette and Marijuana Use And Abusementioning
confidence: 99%
“…Online social communities constitute a significant presence in our lives. Researchers and practitioners are using online data to illuminate many aspects of life including health, politics and culture, based on what people post [1][2][3][4][5]. For example, some studies have focused on recipe websites and shown how food names in online recipes can be a proxy for consumption and dietary patterns of individuals [6].…”
Section: Introductionmentioning
confidence: 99%